Evaluating second language vocabulary and grammar instruction : a synthesis of the research on teaching words, phrases, and patterns - Boers, Frank (New York ; London : Routledge, Taylor & Francis Group, 2021)
"Providing a much-needed critical synthesis of research on teaching vocabulary and grammar to students of a second or foreign language, this book puts the research into perspective in order to distil recommendations for language teaching. Boers evaluates a comprehensive range of both well-established and lesser-known research strands and classroom practices to draw out the most effective instructional approaches to teaching words, multiword expressions, and grammar patterns. Chapters discuss learning as a by-product of communicative activities, language-focused instruction, diverse types of exercises, mnemonic techniques, and more, with a view to building bridges between the available research on such instructional approaches and how they are commonly implemented in actual language courses and textbooks. This book helps teachers make research-informed decisions regarding their instructional approaches to words, phrases, and patterns, and direct researchers to specific areas in need of further inquiry. Boers not only demonstrates how research findings can inform effective teaching, but also calls for a deeper appreciation on the part of researchers of the realities of the teaching profession, making this a worthwhile text for preservice teachers, teacher educators, graduate students and scholars"--
The aim, scope and organization of this book -- Estimating the chances of incidental acquisition -- Enhancing textual input -- From input to output (and back again) -- Evaluating the merits of inferencing and discovery learning -- What practice makes (almost) perfect (and for what purpose)? -- Making it stick -- Taking stock -- Avenues.
OCLC-licensed vendor bibliographic record.
Keywords: Language and languages -- Study and teaching -- Foreign speakers; Second language acquisition; Vocabulary -- Study and teaching; Grammar, Comparative and general -- Study and teaching; Teaching -- Methodology